Medical Education and Social Accountability - İskender Sayek; A. Hilal Batı (Journal of Medical Education and Family Medicine)
The social responsibility of medical schools, whose main goal is to train "good doctors", who are aware of the health problems of society and who protect and improve health, is becoming increasingly important. Social accountability is defined as "the obligation of medical schools to direct their education, research and service activities in a way that meets the priority health needs of the society, region and/or nation they are responsible for serving." Social obligation is addressed at three different levels: social responsibility, social sensitivity and social accountability.In recent years, reviews and reports have been published that offer recommendations for schools that prepare health professionals to clearly link their mission to the health needs of people and to demographic, economic, and cultural changes in society. One of these, the 2010 Global Compact, identified ten areas of action related to a medical school’s responsibility to society. To support medical schools in Turkey in fulfilling their social responsibilities, a national framework defining the "Determinants of Social Responsibility" was prepared by the Association for Evaluation and Accreditation of Medical Education Programs (TEPDAD) with the participation of relevant stakeholders. The social responsibility of medical education is the willingness and ability to adapt to the needs of patients and health care systems, both nationally and globally. It is important for institutions and countries to initiate their obligations to society with an accreditation system that adopts standards based on social responsibility. Accreditation is not only a quality assurance tool but also a force supporting the need for improvement and change. The social obligations of medical education should be included in accreditation processes at all levels.